2011
DOI: 10.4142/jvs.2011.12.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics of pulmonary pneumocystosis and concurrent infections in pigs in Jeju Island, Korea

Abstract: Epidemiological characteristics of swine pulmonary Pneumocystis (P.) carinii and concurrent infections were surveyed on Jeju Island, Korea, within a designated period in 172 pigs submitted from 54 farms to the Department of Veterinary Medicine, Jeju National University. The submitted cases were evaluated by histopathology, immunohistochemistry, PCR/RT-PCR, and bacteriology. P. carinii infection was confirmed in 39 (22.7%) of the 172 pigs. Histopathologically, the lungs had moderate to severe lymphohistioctyic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 17 publications
2
27
1
Order By: Relevance
“…Co-infections in PCS positive pigs have been reported previously. Kim et al (2011) [ 24 ] found that 12.8% of PCS positive pigs were co-infected with PRRSV and 48.7% were co-infected with PCV2 and PRRSV. Furthermore, they identified three PCS positive pigs with concurrent bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Co-infections in PCS positive pigs have been reported previously. Kim et al (2011) [ 24 ] found that 12.8% of PCS positive pigs were co-infected with PRRSV and 48.7% were co-infected with PCV2 and PRRSV. Furthermore, they identified three PCS positive pigs with concurrent bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Cavallini-Sanches et al (2006) [ 18 ] described a rate of 28% in domestic pigs co-infected with Pneumocystis and PCV2, Borba et al (2011) [ 19 ] one of 20.5% in wild boars. Kim et al (2011) [ 20 ] showed 20.5% cases with co-infection with PCV2, 12.8% with PRRSV and 48.7% with both viruses. In human medicine, only a single case report of a patient diagnosed with AIDS and a Pneumocystis pneumonia co-infected with a new genotype of torque teno mini virus has been published so far [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the authors’ knowledge, co-infections with Pneumocystis and bacteria have only been published once in pigs and once in mice so far. Kim et al (2011) [ 20 ] identified three Pneumocystis positive pigs with concurrent bacterial infection. Macy et al (2000) [ 10 ] described a co-infection with P .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the nature of the infectious agents directly or indirectly associated with respiratory diseases in pigs [7,8,11,12]. In one of these studies involving breeding sows in five French farrow-to-finish herds [12], results indicated that S. suis, a secondary pathogen, was quite widespread among sows-67.1% of the animals being positive using a PCR assay-and PCV2 and swIAV infections were highly prevalent (75% of the sows with antibodies against PCV2 and between 91.7% and 100% of the sows with antibodies against swIAV).…”
Section: Bacterium-bacterium Interactions 34 Limitations Of Coinfectmentioning
confidence: 99%